Ироническое начало в фельетоне Киев-город Михаила Булгакова - Bortnowski, Antoni (Studia Rossica Posnaniensia, 2021)
The subject of the article is the analysis of the image of Kiev, presented in Mikhail Bulgakov’s feuilleton Kiev, the City. This work has rarely been the subject of in-depth analysis, despite the fact that it is one of the few texts in which the writer presents the image of his hometown. A characteristic element of the description of Kiev’s past and present is the irony. It is noticeable in the title of the feuilleton, as well as in the names of its parts. The ironic image of Soviet Kiev stands in stark contrast to the vision of the city captured in the novel The White Guard. The analysis of the techniques used by the writer in the text of Kiev, the City (e.g. the naive narrator’s mask, a combination of pompous style and colloquial speech) is carried out in order to prove that the feuilleton, in its style and ideas expressed, also shows the author’s rejection of post-revolutionary reality and his attempt to overcome the trauma of the past through laughter. The ironic image of the Soviet reality on the background of eternal spiritual values makes Kiev, the City a harbinger of the problems covered in Mikhail Bulgakov’s later works.